Entrance lobby with security systems - Ghosh, Ayan (2023)
The entrance lobby is a confluence of raw materials used in construction of the BMC building. The doorways are flanked by marble colonnettes with decorative floral capitals. In addition to iron gates, a variety of security systems are now installed here. Nowadays, this is the entrance through which visitors are screened and allowed inside the building.